A Study on Differences between Professional Endoscopists and Gastroenterologists in Endoscopic Detection and Standard Pathological Biopsy of Inflammatory Bowel Diseases - Dong Yang; Yuqin Li; Haibo Sun; Chuan He; Geng Chen; Zhuo Zhao; Tongyu Tang (Gastroenterology Research and Practice)
Objective. To assess whether professional endoscopists need additional training on inflammatory bowel disease (IBD) diagnosis. Methods. This retrospective study was conducted in patients with IBD, including Crohn’s disease (CD) and ulcerative colitis (UC), which were diagnosed and treated for the first time in our hospital between January 2005 and December 2020. Doctors including gastroenterologists (group G) and professional endoscopists (group E) participated in the study. The data divided into CD or UC and group G or group E were compared. Results. Patients with CD exhibited higher rates of terminal ileal lesions, reexamined colonoscopy within 6 months, and intestinal stenosis than patients with UC (P<0.001). The positive endoscopic IBD diagnosis rate was significantly higher in group G than in group E (89.6% vs. 74.0%, P<0.001). In the subgroup analysis for patients with CD, the positive endoscopic IBD diagnosis rate was significantly higher for group G than for group E (81.5% vs. 41.8%, P<0.001). However, the two groups exhibited no significant difference in the subgroup analysis for patients with UC (94.1% vs. 86.5%, P=0.060). Group G exhibited a higher rate of terminal ileal intubation (83.1% vs. 65.3%, P<0.001) and standard pathological biopsy (72.7% vs. 26.0%, P<0.001) than Group E. Conclusion. Professional endoscopists showed lower rates of terminal ileal intubation, positive endoscopic diagnosis, and standard pathological biopsy than gastroenterologists. Hence, additional training on IBD, particularly on CD, must be provided to professional endoscopists to increase their efficiency for terminal ileal intubation and positive endoscopic diagnosis and to enhance their awareness regarding standard biopsy.